1993
DOI: 10.1002/jbmr.5650080804
|View full text |Cite
|
Sign up to set email alerts
|

Effect of basic fibroblast growth factor on the growth and differentiation of adult stromal bone marrow cells: Enhanced development of mineralized bone-like tissue in culture

Abstract: Rat stromal bone marrow cells (SBMC) were shown to produce mineralized bone-like tissue in culture in the presence of dexamethasone, ascorbic acid, and beta-glycerophosphate. The addition of 3 ng/ml of basic fibroblast growth factor (bFGF) resulted in a significant increase in formation of mineralized tissue. The present study was aimed at assessing the effect of bFGF on the proliferation and differentiation of SBMC and on the sequential development of mineralized bone-like tissue in culture. Transmission elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
56
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 187 publications
(57 citation statements)
references
References 24 publications
1
56
0
Order By: Relevance
“…We attempted to determine the optimal dose of bFGF-2 for periodontal regeneration in dogs from several previous reports. bFGF-2 had a dose-dependent effect on periodontal regeneration at a dose ranging from 0 to 0.16% per implant [3][4][5][6][7][8][9][10][11][12][13][14][15][26][27][28][29] . Hayashi et al reported that new bone formation was smaller in the 0.56% bFGF-2 (100 µg bFGF-2/3×3×2 mm gelatin hydrogel) implant compared to the 0.056% bFGF-2 (10 µg bFGF-2/3×3×2 mm gelatin hydrogel) implant; however, there were no significant differences between them 29) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We attempted to determine the optimal dose of bFGF-2 for periodontal regeneration in dogs from several previous reports. bFGF-2 had a dose-dependent effect on periodontal regeneration at a dose ranging from 0 to 0.16% per implant [3][4][5][6][7][8][9][10][11][12][13][14][15][26][27][28][29] . Hayashi et al reported that new bone formation was smaller in the 0.56% bFGF-2 (100 µg bFGF-2/3×3×2 mm gelatin hydrogel) implant compared to the 0.056% bFGF-2 (10 µg bFGF-2/3×3×2 mm gelatin hydrogel) implant; however, there were no significant differences between them 29) .…”
Section: Discussionmentioning
confidence: 99%
“…New bone formation in the F group was observed along the mesial space onto the distal rootsurface and the distal space onto the mesial root-surface and the new bone had a dimple in the center. It has been reported that the concentration of bFGF-2 regulates the cell proliferation of osteoblasts in vitro 3,30,31) . The present results suggested that bFGF-2 applied on the decalcified dentin surface may promote proliferation and differentiation of osteoblasts near the root surface.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Osteogenic, chondrogenic, and adipocytic lineages represented the mesodermal germ layer. Nodular mineralized deposits characteristic to human osteoblastic cultures derived from bone marrow stromal progenitor cells [30,41] were identified with Alizarin Red S staining in 5 weeks old cultures as described elsewhere [41] (Fig. 3A).…”
Section: Differentiation Capacity Of Homscmentioning
confidence: 97%
“…23 FGF2 can be immobilized on Ti surfaces pretreated with oxygen plasma, 24 and the TiO 2 nanotubular surface benefits drug control release 25 and immobilization of other growth factors such as, bone morphogenetic protein 2 as well.…”
Section: Introductionmentioning
confidence: 99%